Teaching health education: A thematic analysis of early career teachers' experiences following pre-service health training. Issue 3 (3rd April 2017) - Pickett, Karen; Rietdijk, Willeke; Byrne, Jenny; Shepherd, Jonathan; Roderick, Paul; Grace, Marcus
Abstract : Purpose: The purpose of this paper is to understand early career teachers' perceptions of the impact of a pre-service health education programme on their health promotion practice in schools and the contextual factors that influence this. Design/methodology/approach: Semi-structured interviews were conducted with 14 primary and secondary trainee and qualified teachers who had trained at a university in England. Data were analysed using thematic analysis. Findings: The teachers found the training to be a useful introduction, particularly when it was relevant to their practice. They valued gaining practical skills at university, on placement and in school once qualified. They reported that witnessing pupils' lives in school had increased their awareness that health education is important. Their personal qualities, life experience, the school's ethos and competing pressures influenced their practice. Teachers considered that building relationships with colleagues, pupils and parents facilitated health promotion, and that health education needs to be relevant to pupils. Some teachers expressed that teaching about health could be a "minefield". They also discussed whether schools or parents are responsible for educating pupils about health issues and the place of health promotion within education's wider purpose. Originality/value: Few studies have followed-up trainee teachers once they are in teaching posts to explore the longer-term perceived impact of pre-service health education training. The findings suggest that teachers' development takes place via an interaction between training and practice, suggesting that training could particularly aim to provide teachers with a contextualised understanding of health issues and practical experience.